2015
DOI: 10.1111/1541-4337.12124
|View full text |Cite
|
Sign up to set email alerts
|

Thermotolerant Campylobacter during Broiler Rearing: Risk Factors and Intervention

Abstract: Thermotolerant Campylobacters are one of the most important bacterial causative agents of human gastrointestinal illness worldwide. In most European Union (EU) member states human campylobacteriosis is mainly caused by infection with Campylobacter jejuni or Campylobacter coli following consumption or inadequate handling of Campylobactercontaminated poultry meat. To date, no effective strategy to control Campylobacter colonization of broilers during rearing is available. In this review, we describe the public h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 318 publications
(544 reference statements)
1
41
0
1
Order By: Relevance
“…It has been suggested that a reduction of Campylobacter in the chicken intestine by 1 log 10 CFU can reduce the public health risk by 50% to 90%, and a 2 log 10 CFU reduction can reduce the risk by >90% [8,34,35]. This can be achieved with natural compounds [10].…”
Section: Plos Onementioning
confidence: 99%
“…It has been suggested that a reduction of Campylobacter in the chicken intestine by 1 log 10 CFU can reduce the public health risk by 50% to 90%, and a 2 log 10 CFU reduction can reduce the risk by >90% [8,34,35]. This can be achieved with natural compounds [10].…”
Section: Plos Onementioning
confidence: 99%
“…On the other hand, although results of experiments assessing the efficiency of mitigation strategies aimed at increasing resistance to colonization or reducing the level of the pathogen in caeca are encouraging (Meunier et al, 2016;Robyn, Rasschaert, Pasmans, & Heyndrickx, 2015), further studies to obtain more reproducible results are needed before effective applications of those measures on large scale.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Many cases are not reported, and as many as 9 million people are estimated to suffer from campylobacteriosis annually in the EU (Havelaar et al 2013). The cost of campylobacteriosis for the member countries of the European Union is between 500 and 5000 million euros per year (EFSA 2011; Robyn et al 2015). Campylobacter jejuni and C. coli are the most frequently reported species in human cases of Campylobacter infection (WHO (World Health Organisation) 2018), causing approximately 90 and 10% of cases, respectively (Gillespie et al 2002;Nielsen et al 2006;EFSA & ECDC 2018, 2018EFSA 2019EFSA , 2019; Table 1).…”
Section: Introductionmentioning
confidence: 99%